Intellectual Capital Disclosure and Its Implications on Cost of Equity Capital with Information Asymmetry as An Intervening Variable (An Empirical Study on Manufacturing Companies Listed in IDX Year 2012-2014) - Setiawati, Eka; Agustina, Linda (Universitas Negeri Semarang, 2016)
Tujuan penelitian ini adalah menganalisis pengaruh Intellectual Capital Disclosure terhadap Cost of Equity Capital dengan Asimetri Informasi sebagai Variabel Intervening. Populasi penelitian ini adalah seluruh perusahaan manufaktur sektor industri yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2012-2014 sejumlah 148 perusahaan. Teknik pengambilan sampel yang digunakan adalah purposive sampling sehingga menghasilkan 23 perusahaan dengan 69 unit analisis. Teknik analisis data yang digunakan adalah statistik deskriptif dan analisis jalur (path analysis). Hasil penelitian menunjukkan bahwa Intellectual Capital Disclosure tidak berpengaruh secara langsung terhadap Cost of Equity Capital. Selain itu, Intellectual Capital Disclosure melalui Asimetri Informasi tidak berpengaruh terhadap Cost of Equity Capital. Intellectual Capital Disclosure tidak berpengaruh negatif terhadap Asimetri Informasi. Asimetri Informasi berpengaruh signifikan positif terhadap Cost of Equity Capital. Penelitian selanjutnya untuk menambah sampel perusahaan yang terdaftar di Bursa Efek Indonesia (BEI), menambah variabel lain yang dapat mempengaruhi Cost of Equity Capital seperti kebijakan deviden. The purpose of this study was to analyze the effect of Intellectual Capital Disclosure on the Cost of Equity Capital with Information Asymmetry as an intervening variable. The research’s population is the entire industrial sector of manufacturing companies listed in Indonesian Stock Exchange from 2012 to 2014 with total number of 148 companies. The sampling technique used in this research is purposive sampling and the result of purposive sampling 23 industrial enterprises was selected with a total 69 companies for analysis. The data analysis technique used are descriptive statistic and path analysis. The result showed that Intellectual Capital Disclosure has no directly affect on the Cost of Equity Capital. Beside that, Intellectual Capital Disclosure with Information Asymmetry has no affect on the Cost of Equity Capital. Intellectual Capital Disclosure has no effect negative on the Information Asymmetry. Information Asymmetry has effect positive significant on the Cost of Equity Capital. Suggestion for further research is to increase the number of companies listed on the Indonesian Stock Exchange, add the other variable that can affect the Cost of Equity Capital like dividend policy.